2008
DOI: 10.1136/hrt.2008.142588
|View full text |Cite
|
Sign up to set email alerts
|

Explaining trends in coronary heart disease hospitalisations in New Zealand: trend for admissions and incidence can be in opposite directions

Abstract: Recent trends in hospitalisation rates for AMI are significantly influenced by factors other than underlying changes in CHD incidence. Increasing absolute numbers of admissions coded as AMI in New Zealand between 1993 and 2005 can be accounted for by increases in readmissions, increases in interhospital transfers, changes in diagnostic criteria for AMI and in demography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
4
28
0
2
Order By: Relevance
“…[11][12][13][14][15][16][17] Against a declining population with established CHD are recent reports of a flattening of agespecific CHD mortality rates among 35-to 44-year-olds and 45-to 54-year-olds in the United States and United Kingdom, in which increasing rates of overweight and diabetes have been implicated. 11,18 During the study period, age-adjusted mortality rates from CHD fell sharply but at approximately the same rate in the populations with and without CHD, whereas rates of nonfatal MI remained virtually unchanged in both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] Against a declining population with established CHD are recent reports of a flattening of agespecific CHD mortality rates among 35-to 44-year-olds and 45-to 54-year-olds in the United States and United Kingdom, in which increasing rates of overweight and diabetes have been implicated. 11,18 During the study period, age-adjusted mortality rates from CHD fell sharply but at approximately the same rate in the populations with and without CHD, whereas rates of nonfatal MI remained virtually unchanged in both.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that trends of nonfatal MI based on principal discharge diagnoses in the Hospital Morbidity Data ve risk for tota 13 System are valid. 6,7 Further, near complete follow-up (estimated at 99%) was ensured through the well-established data linkage procedures.…”
Section: Briffa Et Al Recurrent Coronary Heart Disease Trends 111mentioning
confidence: 99%
“…Økningen var markant fra midt i 1990-årene og i en tiårs-periode fremover, og den var klart sterkere enn det som kunne forventes som følge av at befolkningen ble eldre. Den ulike utviklingen i ulike aldersgrupper er fortsettelsen av en tendens vi har beskrevet tidligere (1, 2) og som også er funnet i andre land (10). Én forklaring kan vaere følgende: Parallelt med eller endog i forkant av den godt dokumenterte reduksjonen i hjerte-og kardødelighet i Norge som startet i 1970-årene, har det med stor sannsynlighet skjedd en reduksjon i hjerteinfarktinsidensen hos middelaldrende.…”
Section: Materiale Og Metodeunclassified
“…I en nyere studie fra New Zealand er det gjort tilsvarende funn (10). Våre observasjoner er også forenlig med det faktum at den nedadgående tendensen for hjerte-og kardødelighet i denne gruppen har fortsatt på 2000-tallet (11).…”
Section: Materiale Og Metodeunclassified
“…After an early presumptive diagnosis is made rooted in the findings of the history and physical, cardiac testing founds the diagnosis and settles on the practicable competence of the patient, the cruelty of the disease, and the type of threat into a person cataract. With anecdotal levels of aspect and accuracy, diagnostic tests can launch or verify the incidence of obstructions in the coronary arteries, the level of blockages, injure to the heart muscle, swelling of the heart chambers, hereditary heart defects, irregularities of the heart valves, and electrical disorder that interferes with the rhythm of the heartbeat [5][6][7].…”
Section: Introductionmentioning
confidence: 99%